The significant role of religious group’s response to natural disaster in Indonesia: the case of Santri Tanggap Bencana (Santana) - Mohammad Rokib (IAIN Salatiga, 2012)
Natural disasters, which occur regularly in Indonesia, have inspired many volunteergroups to emerge from different groups of society, including religious group.This paper focuses on the experiences of the religious volunteer group calledSantana (Islamic student’s response to disaster) in East Java region. The groupis part of Islamic education institution (pesantren) that emphasizes religious aspectsand attempts to realize religious values in everyday life. The group givesreligious meaning to the experience of disaster and the efforts to help disaster victims. The aim of this study is to describe Santana’s response to natural disasteras not only a natural but also a cultural phenomenon. This study reveals alarge number of religious symbols referring to disaster as natural and theologicalphenomena. Referring to the religious text, disaster victims are categorized bySantana as weak people (mustad’afin). It has inspired this group to engage intheir social activism. Their commitment to the religious tenets involves not onlygiving material aid but also promoting spiritual empowerment. This gives insightinto the dynamic of how religious groups manifest their religious values by providingboth material and spiritual aid.Bencana alam yang terjadi hampir setiap tahun di Indonesia telah mendorongkemunculan kelompok relawan dari berbagai elemen masyarakat, termasukkelompok agama. Artikel ini terfokus pada pengalaman relawan dari kelompokagama bernama Santana (santri tanggap bencana) di Jawa Timur. Kelompokrelawan ini merupakan bagian dari lembaga pesantren yang menekankan aspekkeagamaan serta berusaha merealisasikan nilai-nilai keagamaan dalam kehidupansehari-hari. Kelompok ini memberikan pemaknaan keagamaan pada kejadianbencana alam sekaligus berusaha menolong korban bencana. Tujuan studi iniadalah mendeskripsikan tanggapan kelompok Santana atas bencana alam yangtidak hanya sebagai kejadian alam melainkan juga fenomena (perubahan)kebudayaan. Artikel ini menyatakan bahwa terdapat sebuah gundukan simbolkeagamaan yang menempatkan bencana sebagai peristiwa alam dan fenomenateologis. Dengan merujuk pada teks keagamaan, korban bencana dikategorikanoleh Santana sebagai orang lemah (Mustad’afin). Konsep ini mendorong merekamelakukan aktivisme sosial. Komitmen mereka atas ajaran agama tidak hanyatelah memunculkan pertolongan material tetapi juga penguatan spiritual parakorban bencana.